2023
DOI: 10.3390/ma16093326
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Loose-Fill Thermal Insulation from Wood Scobs Coated with Liquid Glass, Tung Oil, and Expandable Graphite Mixture

Abstract: The current study presents the results of monitoring the behavior of loose-fill thermal insulating material for buildings made of wood scobs (WS), which were coated with one, two, and three component-based coatings from liquid glass (LG), tung oil (TO), and expandable graphite (EG). The thermal conductivity of samples in the dry state and under normal laboratory conditions, short-term water absorption by partial immersion, surface wettability, and water vapor permeability were evaluated, and regression equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The main characteristics of WS were as follows: the average bulk density was 83.0 ± 6.8 kg/m 3 , and the moisture content was 12.1 ± 1.9%. The granulometry of the WS particles can be found in a study by Augaitis et al [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main characteristics of WS were as follows: the average bulk density was 83.0 ± 6.8 kg/m 3 , and the moisture content was 12.1 ± 1.9%. The granulometry of the WS particles can be found in a study by Augaitis et al [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results of thermal conductivity, short-term water absorption, contact angle, and water vapor permeability in [ 34 ] showed that the appropriate multicomponent suspension for the WS coating was LG/TO/EG. However, for the proper and more precise interpretation of the thermal stability and fire resistance results, interim compositions of loose-fill thermal insulation composites WS, WS/LG, WS/LG/TO, and WS/LG/EG were selected, and their compositions are presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By doing so, we can minimise transportation's carbon footprint while also strengthening local economies. It is important to note that produced loose-fill insulating materials may have unique properties due to variations in local resources [76,77] and manufacturing techniques [78,79]. One target of this research is to present some differences, where similar products or identical raw materials used in conjunction with different technologies yield notably different results.…”
Section: Benefits and Challenges Of Loose-fill Insulation In Construc...mentioning
confidence: 99%